PEMANFAATAN PRODUKSI EKSOPOLISAKARIDA DARI Spirulina sp. SEBAGAI ADSORBEN ION PB(II) DAN CD(II) DALAM LARUTAN - Widyastuti , Widyastuti (Jurnal Kelitbangan Bappeda Pringsewu, 2019)
In this research, it has been carried out adsorption process of Pb(II) and Cd(II) ions toward adsorbent of exopolysaccharide (EPS). The material obtained from synthesis result was characterized by spectrophotometer infrared (IR) to identify functional groups and scanning electron microscope-energy dispersive x-ray (SEM-EDX to investigate surface morphology. Determination of metal ion concentration was performed by inductively coupled plasma-atomic emission spectrometry (ICP-AES). Adsorption of Pb(II) and Cd(II) ions with EPS is optimum at pH 7 and consentration at 25 ppm with the capasities adsorption of 91.61and 82.04% at 4Â°C and contact time of 15 min.